Critical indexes of compositional nutrient diagnosis (CND) and its validation in wheat fields - Geiklooi, Abolfazl; Reyhanitabar, Adel; Najafi, Nosratollah (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Plant nutrient composition can be used as an evaluation criterion for optimum plant growth. The objectives of present study were to (a) derive critical compositional nutrient (CND) norms for survived wheat fields and sufficiency ranges as CND nutrient index for validation samples, (b) provide a squared CND threshold nutrient imbalance index (CND r2) and compare with DRIS nutrient imbalance indices, (c) determine balanced nutrients concentration with CND indices. The yield cutoff value was 4,232 kg.ha-1. The CND indexes results indicate that Zn is the most deficient nutrient in wheat, followed by Cu, Fe, Mn and B, whereas N is the most excessive nutrient, followed by K, Ca, Mg and P. In the validation trials, the yield cutoff value were reported 5,023 kg.ha-1. The calculated CND r2 in the validation population was lower than that of the survey wheat fields, indicating a more balanced concentration of nutrients due to the application of fertilizer treatments. Significant principal component (PC) loadings were obtained after the varimax rotation. The first three PCs in high- and low-yielding subgroups and whole data set indicated 52.8, 54.6 and 48.8 % total variance, respectively This study revealed that the decline in the wheat yield was due to the nutrient imbalance associated with multi nutrient deficiency (Zn, Cu, Fe, Mn and B) and multi nutrient excess (N, K, Ca, Mg and P).Keywords: compositional nutrient diagnosis (CND), diagnosis and recommendation integrated system (DRIS), nutrients composition, principal component analysis (PCA).